Perancangan Aplikasi Alumni untuk Mendukung Akreditasi (Studi Kasus: Jurusan TI PNP) - Dwiny Meidelfi; Meri Azmi; Ronal Hadi; Wina Rahma Fitri (Prosiding SISFOTEK, 2018)
Alumni are an important asset for universities that must be embraced and developed. Alumni can provide a various constructive inputs to universities and are expected to be able to develop networks outside the agency and improve the good image of the almamater to the community. A college should provide a forum that can provide data of alumni for evaluating educational outcomes and improving quality to prepare accreditation assessment. An alumni application system that is able to recap all of alumni data and other data needed will certainly improve the accreditation assessment results. Based on these problems, we need an alumni application that can solve the problems effectively and efficiently. In this study a web-based alumni application was designed using the Unified Modeling Language (UML) method based on the points of the diploma study program accreditation assessment points by the National Accreditation Board of Higher Education (BAN-PT). The final product of this research is the design application of information technology’s alumni at Politeknik Negeri Padang. Based on the results of the testing design, this application is effectively used to manage alumni data and match with the alumni data management standards contained in the evaluation standard of the diploma accreditation chapter evaluation of graduates.